Micromammal and macromammal stable isotopes from a MIS 6 fossil hyena den (Pinnacle Point site 30, south coast, South Africa) reveal differences in relative contribution of C-4 grasses to local and regional palaeovegetation on the Palaeo-Agulhas Plain - Williams, HM; Lee-Thorp, JA; Matthews, T; Marean, CW (Elsevier, 2020)
Proxy records dating to marine isotope stage 6 on the south coast of South Africa are rare. This study presents integrated micromammal and macromammal stable isotope palaeoenvironmental proxy data from one of the few MIS 6 fossil occurrences in the region, a fossil brown hyena (Parahyena brunnea) den, Pinnacle Point 30 (PP30). Two predators with significantly different foraging ranges aggregated the large and small mammal components of the PP30 fossil assemblage. The large mammal specimens were brought to PP30 by Parahyena brunnea with an expansive daily foraging radius that focused on the Palaeo-Agulhas Plain. The micromammal taxa were deposited at the site primarily by the spotted eagle owl, Bubo africanus, with a foraging radius of ∼3 km, and would have sampled the ecotone between the Palaeo-Agulhas Plain and the Cape coastal lowlands. The large and small mammal components of the PP30 assemblage thus sample palaeovegetation at different geographic scales; micromammal stable isotope data act as a proxy for local conditions, while macromammal data integrate information at a broader scale. Comparison of the stable carbon isotope data obtained from the micromammal and macromammal fossil specimens suggests that these two assemblage components intersected vegetation with differing proportions of C-4 grasses. Micromammal δ13C proxy data indicates that, immediately local to the site, a C-3 dominated vegetation was present, while the large mammal δ13C proxy data shows evidence of a vegetation community with a greater C-4 grass component that likely occurred somewhat more distant from the site itself on the Palaeo-Agulhas Plain.